Caregivers' Priorities and Observed Outcomes of Attention-Deficit Hyperactivity Disorder Medication for Their Children. Issue 2 (February 2018) - Ross, Melissa; Nguyen, Vy; Bridges, John F. P.; Ng, Xinyi; Reeves, Gloria; Frosch, Emily; dosReis, Susan
ABSTRACT: Objective: To document variability among caregivers' priorities when considering medication to treat their Children's attention-deficit hyperactivity disorder (ADHD) and explore associations between these priorities and medication-related improvements. Methods: Caregivers of children, ages 4 to 14 years, diagnosed with ADHD were recruited from outpatient clinics and support groups across Maryland. A survey gathered data on caregiver-reported concerns when considering ADHD medication, demographic characteristics, and observed and desired improvements in their child's ADHD. A validated Best-Worst Scaling instrument assessed priorities among 16 concerns when considering ADHD medication. Latent class analysis identified subgroups with similar ADHD medication concerns. Differences in self-reported medication-related improvements were examined across subgroups. Results: The 184 participants (mean = 42 yrs) were primarily the biological mother, 68% white and 25% black. Their children were mostly male (73%) and using medication (81%). Overall, the most important ADHD medication concerns were the child becoming a successful adult ( p < 0.0001), school behavior improvements ( p < 0.0001), and better grades ( p < 0.0001). Others thinking badly of the child was a significantly less important concern ( p < 0.0001). Three subgroups were identified: short-term outcomes-oriented group (39%), long-term outcomes-oriented group (37%), and side effects/safety-oriented group (27%). Relative to the other 2 groups, a smaller proportion of the side effects/safety-oriented group desired these improvements ( p < 0.2618). Conclusion: Most caregivers prioritize short- and long-term outcomes when considering ADHD medication. However, those most concerned with long- or short-term outcomes tended to desire additional improvements in their child's ADHD.